Ceramic membrane anti-fouling membrane layer for sewage treatment and preparation process thereof

Through the high-energy ball milling of ceramic powder and nano titanium dioxide and the multi-component combination, the ceramic film anti-fouling film layer is prepared, which solves the problem of the influence of pollutants in wastewater treatment, and achieves a long-term good anti-fouling effect and mechanical strength. promote.

CN119258806APending Publication Date: 2025-01-07GUANGXI GREEN LEVER ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411504125.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing ceramic membranes are susceptible to various pollutants in wastewater treatment, resulting in membrane pollution, reduced filtration performance and shortened service life. In addition, traditional preparation processes lead to uneven distribution of membrane porosity and pore size, making it difficult to deal with complex wastewater components. .

Method used

Ceramic film anti-fouling film is prepared by high-energy ball milling, mixing and stirring, cast film liquid preparation and phase conversion method using ceramic powder, nano-titanium dioxide, polyether sulfone, surfactant, antibacterial agent, tea polyphenol powder and organic solvent. The layer is dried and heat-treated to form a uniform film layer structure to improve soil resistance.

Benefits of technology

Effectively inhibit microbial growth, enhance antioxidant and adsorption capabilities, extend the service life of ceramic membranes, improve mechanical strength and stability, and ensure good filtration effect and anti-fouling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258806A_ABST
    Figure CN119258806A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic membrane anti-pollution membrane layers, in particular to a ceramic membrane anti-pollution membrane layer for sewage treatment and a preparation process of the ceramic membrane anti-pollution membrane layer. The ceramic material comprises the following raw materials: ceramic powder; nano titanium dioxide; polyether sulfone; a surfactant; an antibacterial agent; an organic solvent; tea polyphenol powder; after the ceramic powder and the nanometer titanium dioxide are subjected to high-energy ball milling to reach the nanometer level, the specific surface area is increased, the silver ion antibacterial agent is continuously released, growth and reproduction of microorganisms on the surface of the membrane are effectively inhibited, biological pollution and blockage are reduced, various components in the tea polyphenol powder act synergistically, the effects of resisting oxidation, resisting bacteria and adsorbing organic pollutants are achieved, and meanwhile, the effect of resisting bacteria is achieved. The stability and solubility of the tea polyphenol powder are further improved through secondary combination of the citric acid, the ceramic powder and the nano titanium dioxide, the overall anti-pollution performance is enhanced, the membrane layer can keep a good anti-pollution effect for a long time in sewage treatment, the service life of the ceramic membrane is effectively prolonged, and the maintenance cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic membrane anti-fouling membrane layers, and in particular to a ceramic membrane anti-fouling membrane layer for sewage treatment and a preparation process thereof. Background Art

[0002] With the development of industry and the growth of population, the problem of sewage treatment is becoming increasingly serious. Traditional sewage treatment methods have gradually exposed some shortcomings in terms of treatment efficiency, cost and environmental friendliness. In the sewage treatment process, ceramic membranes have received extensive attention due to their excellent chemical stability, mechanical strength and high temperature resistance. However, ceramic membranes are easily affected by various pollutants during use, resulting in membrane pollution problems and reducing the filtration performance and service life of the membrane.

[0003] On the one hand, the existing ceramic membrane anti-fouling materials are single and difficult to cope with complex sewage components. For example, some ceramic membranes rely only on a single antibacterial agent or surfactant to improve their anti-fouling performance, with limited effect. On the other hand, there are many types of pollutants in sewage, including organic matter, microorganisms, heavy metal ions, etc. A single anti-fouling method is difficult to comprehensively and effectively deal with these pollutants. At the same time, traditional preparation processes may lead to uneven porosity and pore size distribution of the membrane layer, affecting the filtration effect and anti-fouling performance. There may also be poor stability, which makes the ceramic membrane prone to fouling and damage when facing complex sewage environments, shortening its service life, thereby increasing the cost and difficulty of sewage treatment.

[0004] In view of this, there is an urgent need for a ceramic membrane anti-fouling membrane layer for sewage treatment and a preparation process thereof to improve the deficiencies of the existing technology. Summary of the invention

[0005] The object of the present invention is to provide a ceramic membrane anti-fouling membrane layer for sewage treatment and a preparation process thereof, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, on the one hand, the present invention provides a ceramic membrane anti-fouling membrane layer for sewage treatment, comprising the following raw materials:

[0007] Ceramic powder: 40-60 parts;

[0008] Nano titanium dioxide: 8-17 parts;

[0009] Polyethersulfone: 12-20 parts;

[0010] Surfactant: 1-3 parts;

[0011] Antibacterial agent: 0.8-2 parts;

[0012] Organic solvent: 1-3 parts;

[0013] Tea polyphenols powder: 6-12 parts.

[0014] As a further improvement of the technical solution, the antibacterial agent is a silver ion antibacterial agent; the surfactant is sodium dodecyl sulfate; and the organic solvent is N,N-dimethylformamide.

[0015] As a further improvement of the technical solution, the ingredients of the tea polyphenol powder include catechins, flavonoids and flavonols, phenolic acids, anthocyanins and citric acid, wherein the amount of citric acid in the tea polyphenol powder is 5%-15%.

[0016] On the other hand, the present invention also provides a process for preparing a ceramic membrane anti-fouling membrane layer for sewage treatment, comprising the following steps:

[0017] S1. Raw material pretreatment: putting ceramic powder and nano titanium dioxide into a high-energy ball mill for grinding to make the particle size of ceramic powder and nano titanium dioxide reach nanometer level;

[0018] S2. Mixing and stirring: Add the pretreated ceramic powder and nano titanium dioxide, as well as polyethersulfone, surfactant, antibacterial agent and tea polyphenol powder into a clean stirring container in sequence, then add the organic solvent, stir with a stirrer, and check the uniformity of the mixed material by sampling and testing;

[0019] S3, preparation of casting solution: transferring the mixed materials to a heating container for heating, stirring the materials continuously during the heating process to fully dissolve the polyethersulfone to form a casting solution, and then transferring the casting solution to a vacuum degassing device for vacuum degassing to remove bubbles in the casting solution, and controlling the vacuum degree and degassing time;

[0020] S4, membrane preparation: a ceramic membrane anti-fouling membrane layer is prepared by a phase inversion method, the casting liquid is uniformly coated on a support, and then the support coated with the casting liquid is immersed in a coagulation bath, the temperature of the coagulation bath is 10°C-30°C, so that the solvent in the casting liquid is exchanged with the non-solvent in the coagulation bath, thereby forming a membrane layer with a microporous structure;

[0021] S5, post-treatment: taking the prepared film layer out of the coagulation bath, placing it in a well-ventilated drying oven for drying, controlling the drying temperature and time, removing the residual solvent, and then heat-treating the dried film layer, placing the film layer in a heat treatment device, and controlling the temperature and time, and then using a plasma treatment device to perform surface modification on the heat-treated film layer to introduce hydrophilic groups;

[0022] S6. Performance testing: Conduct comprehensive performance testing on the prepared ceramic membrane anti-fouling film layer, including porosity, pore size distribution, anti-fouling performance and mechanical strength.

[0023] As a further improvement of the technical solution, in S1, the rotation speed of the high-energy ball mill is 300r / min-400r / min, and the grinding time is 4h-6h.

[0024] As a further improvement of the technical solution, in S2, the stirring time of the agitator is 2h-4h, the stirring speed of the agitator is 100r / min-200r / min, and the state of the mixed material is observed every 30min-40min.

[0025] As a further improvement of the technical solution, in S3, the temperature of the heating container is controlled at 60°C-80°C, and the material is continuously stirred for 1h-2h.

[0026] As a further improvement of the present technical solution, in S3, the vacuum degree of the vacuum degassing equipment is -0.06MPa--0.1MPa, and the degassing time is 40min-60min.

[0027] As a further improvement of the technical solution, in S5, the drying temperature of the drying oven is 40°C-60°C, and the drying time is 5h-7h.

[0028] As a further improvement of the technical solution, in S5, the temperature of the heat treatment equipment is controlled at 100°C-150°C, and the heat treatment time is controlled at 1h-2h.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. In the anti-fouling membrane layer of the ceramic membrane used for sewage treatment and its preparation process, after the ceramic powder and nano-titanium dioxide are milled to the nano level through high-energy ball milling, the specific surface area is increased, and they are fully in contact with other components and evenly dispersed in the membrane layer. The silver ion antibacterial agent is continuously released, which effectively inhibits the growth and reproduction of microorganisms on the membrane surface and reduces biological fouling. The various components in the tea polyphenol powder work synergistically to exert the effects of antioxidant, antibacterial and adsorption of organic pollutants. At the same time, the secondary combination of citric acid with ceramic powder and nano-titanium dioxide further improves the stability and solubility of the tea polyphenol powder, enhances the overall anti-fouling performance, and enables the membrane layer to maintain a good anti-fouling effect for a long time in sewage treatment, effectively prolongs the service life of the ceramic membrane, and reduces maintenance costs.

[0031] 2. In the anti-fouling membrane layer of the ceramic membrane used for sewage treatment and its preparation process, the synergistic effect of multiple components and the control of preparation time, temperature, etc. ensure that the polyethersulfone is fully dissolved to form a uniform casting liquid. The vacuum degassing treatment effectively removes bubbles and improves the quality of the membrane layer. The phase inversion preparation and post-treatment further optimize the membrane layer structure to give it good porosity and pore size distribution, so that it can filter pollutants during sewage treatment. At the same time, the improved mechanical strength ensures the durability of the membrane layer during use, and the enhanced stability also reduces the risk of membrane damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a flowchart of the process for preparing the anti-fouling membrane layer of the ceramic membrane used for sewage treatment of the present invention;

[0033] Figure 2 It is a line graph of the antifouling property, mechanical strength, porosity and pore size distribution of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0035] An embodiment of the present invention provides a ceramic membrane anti-fouling membrane layer for sewage treatment, comprising the following raw materials:

[0036] Ceramic powder: 40-60 parts;

[0037] Nano titanium dioxide: 8-17 parts;

[0038] Polyethersulfone: 12-20 parts;

[0039] Surfactant: 1-3 parts; the surfactant is sodium dodecyl sulfate, which has good dispersibility and can make ceramic powder, nano titanium dioxide and other particles evenly dispersed in the organic solvent to prevent particle agglomeration, thereby improving the uniformity and performance stability of the film layer. Secondly, sodium dodecyl sulfate has a certain emulsification effect, which can help the organic solvent and other components to mix better to form a uniform casting solution, which is conducive to the preparation of the subsequent film layer;

[0040] Antimicrobial agent: 0.8-2 parts; the antimicrobial agent uses silver ion antimicrobial agent, which has a broad-spectrum antimicrobial property and can inhibit and kill a variety of microorganisms such as bacteria, fungi and viruses. In the anti-fouling film layer of the ceramic membrane, silver ions can be continuously released, effectively inhibiting the growth and reproduction of microorganisms on the membrane surface, reducing biological fouling, thereby improving the anti-fouling performance and service life of the ceramic membrane. At the same time, the silver ion antimicrobial agent is relatively stable, not easy to volatilize and decompose, and can maintain the antibacterial effect for a long time. In addition, the silver ion antimicrobial agent can play a significant antibacterial role at a lower concentration and will not cause greater harm to the environment and human health;

[0041] Organic solvent: 1-3 parts; the organic solvent is N,N-dimethylformamide, which has good solubility for ceramic powder, nano-titanium dioxide, polyethersulfone and other ingredients, and can promote uniform mixing of various ingredients to form a stable casting solution;

[0042] Tea polyphenol powder: 6-12 parts; the ingredients of tea polyphenol powder include catechins, flavonoids and flavonols, phenolic acids, anthocyanins and citric acid, wherein the amount of citric acid in the tea polyphenol powder is 5%-15%. The addition of citric acid helps to improve the stability and solubility of the tea polyphenol powder. At the same time, in synergistic effect with other ingredients, the anti-fouling performance of the tea polyphenol powder in the preparation of the anti-fouling membrane layer of the sewage treatment ceramic membrane is enhanced. These ingredients work together to enable the tea polyphenol powder to play a variety of functions such as antioxidant, antibacterial, and adsorption of organic pollutants in the sewage treatment process, thereby improving the anti-fouling ability and service life of the ceramic membrane.

[0043] according to Figure 1 As shown, the embodiment of the present invention also provides a preparation process for preparing the above-mentioned ceramic membrane anti-fouling membrane layer for sewage treatment, comprising the following steps:

[0044] Step 1: Raw material pretreatment: put ceramic powder and nano titanium dioxide into a high-energy ball mill for grinding. The speed of the high-energy ball mill is 300r / min-400r / min, and the grinding time is 4h-6h, so that the particle size of the ceramic powder and nano titanium dioxide reaches the nanometer level, which can increase the specific surface area of ​​the material and increase the contact area with other components, thereby improving its activity;

[0045] Step 2, mixing and stirring: the pretreated ceramic powder and nano titanium dioxide, as well as polyethersulfone, surfactant, antibacterial agent and tea polyphenol powder are added to a clean stirring container in sequence, and then an organic solvent is added, and a stirrer is used for stirring. The stirring time of the stirrer is 2h-4h, which can make the ceramic powder, nano titanium dioxide, polyethersulfone, surfactant, antibacterial agent, tea polyphenol powder and the like fully mixed with the organic solvent to achieve a uniform state, thereby ensuring the stability of the performance of the film layer in the subsequent preparation process. The stirring speed of the stirrer is 100r / min-200r / min, which is conducive to the full dispersion of each component in the organic solvent without being too intense to cause material splashing or generate too much heat. The state of the mixed material is observed every 30min-40min, and possible problems such as material agglomeration, incomplete dissolution, etc. can be discovered in time, so as to adjust the stirring parameters in time or take other measures to make the components fully mixed and uniform, improve the quality and performance of the anti-fouling film layer of the ceramic membrane, and check the uniformity of the mixed material by sampling and testing;

[0046] Step 3, preparation of casting liquid: the mixed material is transferred to a heating container for heating, the temperature of the heating container is controlled at 60°C-80°C, and a thermometer is used to monitor the temperature change in real time. During the heating process, the material is continuously stirred for 1h-2h to ensure that the polyethersulfone is fully dissolved, and it also helps to better mix the various components during the heating process, so that the polyethersulfone is fully dissolved to form a casting liquid, and then the casting liquid is transferred to a vacuum degassing device for vacuum degassing treatment, and the vacuum degree and degassing time are controlled. The vacuum degree of the vacuum degassing device is -0.06MPa--0.1MPa, and the degassing time is 40min-60min, and the bubbles in the casting liquid are removed to improve the quality of the film layer;

[0047] Step 4, membrane preparation: The ceramic membrane anti-fouling membrane layer is prepared by the phase inversion method, and the casting liquid is evenly coated on the support body. The support body can be made of non-woven fabric or porous ceramics, and its surface is ensured to be clean and flat. Then, the support body coated with the casting liquid is immersed in a coagulation bath. The temperature of the coagulation bath is 10°C-30°C, so that the solvent in the casting liquid is exchanged with the non-solvent in the coagulation bath, thereby forming a membrane layer with a microporous structure, and the formation process of the membrane layer is observed to ensure the uniformity and stability of the microporous structure;

[0048] Step 5, post-treatment: take the prepared film layer out of the coagulation bath, place it in a well-ventilated drying oven for drying, control the drying temperature and time, the drying temperature of the drying oven is 40℃-60℃, the drying time is 5h-7h, remove the residual solvent, and then heat-treat the dried film layer, put the film layer into a heat treatment device, and control the temperature and time. The temperature of the heat treatment device is controlled at 100℃-150℃, and the heat treatment time is controlled at 1h-2h. The heat treatment process can improve the strength and stability of the film layer, and promote the interaction between the components. Then use a plasma treatment device to perform surface modification on the heat-treated film layer, introduce hydrophilic groups, and improve the anti-fouling performance of the film layer;

[0049] Step 6. Performance testing: Conduct comprehensive performance testing on the prepared ceramic membrane anti-fouling film layer, including porosity, pore size distribution, anti-fouling performance and mechanical strength.

[0050] In the present invention, firstly, ceramic powder and nano titanium dioxide are subjected to high-energy ball milling treatment to make their particle size reach the nanometer level, which can not only increase the specific surface area of ​​the material, increase the contact area with other components, and thus improve its activity; at the same time, the nanometer-level ceramic powder and titanium dioxide can be dispersed in the casting liquid to form a uniform film layer structure. For example, in the subsequent mixing and stirring, casting liquid preparation and film layer preparation process, the nanometer-level particles can be fully combined with polyethersulfone, surfactant, antibacterial agent, tea polyphenol powder, etc., to improve the uniformity and performance stability of the film layer, and can also effectively improve the anti-fouling performance, mechanical strength and other comprehensive effects of the ceramic film anti-fouling film layer;

[0051] Among them, the citric acid in the tea polyphenol powder can be secondary combined with ceramic powder and nano-titanium dioxide. The reaction mechanism is mainly that the functional groups such as carboxyl in citric acid can form hydrogen bonds or other weak interactions with the hydroxyl groups on the surface of ceramic powder and nano-titanium dioxide. For example, the carboxyl group (-COOH) of citric acid can react with the hydroxyl group (-OH) on the surface of ceramic powder: R-COOH+M-OH→R-COO-M+H2O (where R represents the partial structure of citric acid, and M represents ceramic powder or nano-titanium dioxide), which can improve the stability and solubility of tea polyphenol powder in the film layer, and at the same time, synergize with other ingredients to enhance the anti-fouling performance.

[0052] After ceramic powder and nano-titanium dioxide are milled to the nano level through high-energy ball milling, the specific surface area is increased, fully in contact with other ingredients, and evenly dispersed in the membrane layer. The silver ion antibacterial agent is continuously released, which effectively inhibits the growth and reproduction of microorganisms on the membrane surface and reduces biological fouling. The various ingredients in the tea polyphenol powder work synergistically to exert antioxidant, antibacterial and organic pollutant adsorption effects. At the same time, the secondary combination of citric acid with ceramic powder and nano-titanium dioxide further improves the stability and solubility of the tea polyphenol powder and enhances the overall anti-fouling performance, so that the membrane layer can maintain a good anti-fouling effect for a long time in sewage treatment, effectively extending the service life of the ceramic membrane and reducing maintenance costs.

[0053] The synergistic effect of multiple ingredients and the control of preparation time, temperature, etc. ensure that polyethersulfone is fully dissolved to form a uniform casting solution. Vacuum degassing treatment effectively removes bubbles and improves the quality of the membrane layer. Phase inversion preparation and post-treatment further optimize the membrane structure to give it good porosity and pore size distribution, thereby being able to filter pollutants during sewage treatment. At the same time, the improved mechanical strength ensures the durability of the membrane during use, and the enhanced stability also reduces the risk of membrane damage.

[0054] According to different raw material dosages, the ceramic membrane anti-fouling membrane layer for sewage treatment provided by the present invention is further described through the following specific examples.

[0055] Example 1

[0056] Ingredients: 45 parts of ceramic powder, 17 parts of nano titanium dioxide, 15 parts of polyethersulfone, 2 parts of surfactant, 1 part of antibacterial agent, 2 parts of organic solvent, 8 parts of tea polyphenol powder;

[0057] Preparation process:

[0058] Raw material pretreatment: ceramic powder and nano-titanium dioxide were placed in a high-energy ball mill and ground at a speed of 350 r / min for 5 h;

[0059] Mixing and stirring: Add the pretreated materials into the stirring container in sequence, add the organic solvent, stir at a speed of 150r / min for 3h, observe the state of the mixed material every 35min, and sample and test the uniformity;

[0060] Preparation of casting solution: The temperature of the heating container is controlled at 70°C, the material is stirred continuously for 1.5 hours, the vacuum degree of the vacuum degassing equipment is -0.08MPa, and the degassing time is 50min;

[0061] Membrane preparation: Coat the casting solution on the porous ceramic support and immerse it in a coagulation bath at a temperature of 20°C.

[0062] Post-treatment: drying oven temperature 50°C, drying time 6h; heat treatment equipment temperature 120°C, heat treatment time 1.5h, and finally plasma treatment;

[0063] Performance testing: testing porosity, pore size distribution, anti-fouling performance and mechanical strength.

[0064] Example 2

[0065] Ingredients: 50 parts of ceramic powder, 12 parts of nano titanium dioxide, 18 parts of polyethersulfone, 2.5 parts of surfactant, 1.2 parts of antibacterial agent, 2.5 parts of organic solvent, 10 parts of tea polyphenol powder;

[0066] Preparation process:

[0067] Raw material pretreatment: grind ceramic powder and nano-titanium dioxide at a speed of 380 r / min for 5.5 h;

[0068] Mixing and stirring: Stir at 180r / min for 3.5h, observe every 38min;

[0069] Preparation of casting solution: heat to 75°C, stir for 1.8h, vacuum degree -0.09MPa, degassing for 55min;

[0070] Membrane preparation: coated on a non-woven fabric support, coagulation bath temperature 25°C;

[0071] Post-treatment: drying temperature 55°C, time 6.5h; heat treatment temperature 130°C, time 1.8h, plasma treatment;

[0072] Performance test: Same as Example 1.

[0073] Example 3

[0074] Ingredients: 48 parts of ceramic powder, 15 parts of nano titanium dioxide, 16 parts of polyethersulfone, 1.8 parts of surfactant, 1.5 parts of antibacterial agent, 1.8 parts of organic solvent, 9 parts of tea polyphenol powder;

[0075] Preparation process:

[0076] Raw material pretreatment: grinding at 360r / min for 4.5h;

[0077] Mixing and stirring: 160r / min stirring for 3.2h, observation every 32min;

[0078] Preparation of casting solution: heating at 72°C, stirring for 1.6h, vacuum degree -0.07MPa, degassing for 45min;

[0079] Membrane preparation: coated on a porous ceramic support, coagulation bath temperature 18°C;

[0080] Post-treatment: drying temperature 52°C, time 6h; heat treatment temperature 115°C, time 1.6h, plasma treatment;

[0081] Performance test: Same as Example 1.

[0082] Example 4

[0083] Ingredients: 55 parts of ceramic powder, 10 parts of nano titanium dioxide, 19 parts of polyethersulfone, 2.8 parts of surfactant, 1.8 parts of antibacterial agent, 2.8 parts of organic solvent, 11 parts of tea polyphenol powder;

[0084] Preparation process:

[0085] Raw material pretreatment: grinding at 400r / min for 6h;

[0086] Mixing and stirring: 190r / min for 4h, observe every 40min;

[0087] Preparation of casting solution: heating at 80℃, stirring for 2h, vacuum degree -0.1MPa, degassing for 60min;

[0088] Membrane preparation: coated on non-woven fabric support, coagulation bath temperature 30°C;

[0089] Post-treatment: drying temperature 60°C, time 7h; heat treatment temperature 150°C, time 2h, plasma treatment;

[0090] Performance test: Same as Example 1.

[0091] Table 1 Amount of each raw material used in Examples 1-4 (parts)

[0092] Example 1 Example 2 Example 3 Example 4 Ceramic powder (parts) 45 50 48 55 Nano titanium dioxide (parts) 17 12 15 10 Polyethersulfone (parts) 15 18 16 19 Surfactant (part) 2 2.5 1.8 2.8 Antimicrobial agent (parts) 1 1.2 1.5 1.8 Organic solvent (parts) 2 2.5 1.8 2.8 Tea polyphenols powder (part) 8 10 9 11

[0093] In order to verify that the ceramic membrane anti-fouling film layer prepared in the embodiment of the present invention has good anti-fouling property and mechanical strength, the ceramic membrane anti-fouling film layer for sewage treatment provided in the embodiment of the present invention is described by the following test examples.

[0094] Test example

[0095] The purpose of this test group is to explore the effects of different component ratios on the anti-fouling film layer of the ceramic membrane.

[0096] Test objective: To detect the anti-fouling property, mechanical strength, porosity and pore size distribution of the anti-fouling membrane layer of the ceramic membrane of the present invention.

[0097] Test method: Test group A, test group B, test group C and test group D respectively use the composition ratios of the ceramic membrane anti-fouling membrane layer materials provided in Examples 1-4; the control example uses control group A, control group B, control group C and control group D, wherein:

[0098] Control group A

[0099] Ingredients: 40 parts of ceramic powder, 8 parts of nano titanium dioxide, 12 parts of polyethersulfone, 1 part of surfactant, 0.8 parts of antibacterial agent, 1 part of organic solvent, tea polyphenol-free powder;

[0100] Preparation process: Similar to Example 1, but without adding tea polyphenol powder related steps.

[0101] Control group B

[0102] Ingredients: 60 parts of ceramic powder, 17 parts of nano titanium dioxide, 20 parts of polyethersulfone, 3 parts of surfactant, 2 parts of antibacterial agent, 3 parts of organic solvent, 12 parts of tea polyphenol powder, but there is no citric acid in the tea polyphenol powder;

[0103] Preparation process: Similar to Example 1, but the ingredients of tea polyphenols powder are different.

[0104] Control group C

[0105] Ingredients: 65 parts of ceramic powder, 5 parts of nano titanium dioxide, 26 parts of polyethersulfone, 3 parts of surfactant, 0.5 parts of antibacterial agent, 2.8 parts of organic solvent, 2 parts of tea polyphenol powder;

[0106] Preparation process: Similar to Example 1.

[0107] Control group D

[0108] Ingredients: Traditional ceramic membrane material ingredients, such as 50 parts of ceramic powder, 10 parts of conventional additives (such as polyvinyl alcohol, etc.), without special ingredients such as nano titanium dioxide and tea polyphenol powder;

[0109] Preparation process: Raw material mixing: simply mix the ceramic powder and conventional additives; use the traditional pressing molding process to prepare the membrane layer, without special casting liquid preparation and phase conversion method; post-processing: only simple drying, without heat treatment and plasma treatment; performance testing: test porosity, pore size distribution, anti-fouling performance and mechanical strength.

[0110] Table 2 Test indicators of each sample

[0111]

[0112]

[0113] According to Table 2, the above comparison data are summarized as follows:

[0114] In terms of anti-fouling property: the anti-fouling property of the test group (Examples 1-4) is significantly better than that of the control group. The anti-fouling property of the test group AD is between 85% and 90%, while the anti-fouling property of the control group AD is only 74% at the highest and 48% at the lowest. Among them, the control group D (traditional ceramic membrane material) has the worst anti-fouling property. The anti-fouling performance of the test group with the addition of tea polyphenol powder and specific component ratios and processes is improved. The anti-fouling property of the control group A is significantly lower than that of the test group because no tea polyphenol powder is added. The control group B does not contain citric acid in the tea polyphenol powder, and its anti-fouling property is also lower than that of the test group. The proportion of components in the control group C is not reasonable and the amount of tea polyphenol powder is small, so its anti-fouling property is also weak.

[0115] In terms of mechanical strength: the mechanical strength of the experimental group was also higher than that of the control group. The mechanical strength of the experimental group AD was between 81% and 88%, while the mechanical strength of the control group AD was 72% at the highest and 50% at the lowest. High-energy ball milling treatment, optimized component ratios and post-processing processes (such as heat treatment and plasma treatment) improved the mechanical strength of the experimental group. The control group D used traditional pressing molding technology without special post-processing steps, and had the worst mechanical strength.

[0116] Porosity: The porosity of the experimental group was higher than that of the control group, ranging from 39% to 44%, while the highest porosity of the control group was 36% and the lowest was 20%. The use of phase inversion method and strict control of process parameters were helpful to improve the porosity. The porosity of the membrane layer prepared by traditional process in the control group D was lower.

[0117] In terms of pore size distribution: the experimental group has better pore size distribution, ranging from 85% to 92%, while the control group has a maximum of 76% and a minimum of 50%; the controlled preparation process and the synergistic effect of the ingredients make the pore size distribution of the experimental group more uniform, while the pore size distribution of the membrane layer prepared by the traditional process in the control group D is poor.

[0118] It can be seen that controlling the proportion of ceramic powder, nano-titanium dioxide, polyethersulfone, surfactant, antibacterial agent, organic solvent and tea polyphenol powder, and adopting a series of steps such as high-energy ball milling, mixing and stirring, casting liquid preparation, phase inversion membrane preparation and post-treatment process (including drying, heat treatment and plasma treatment) has better effect than the control group. The addition of tea polyphenol powder and citric acid therein can effectively improve the anti-fouling performance, making the anti-fouling property between 85% and 90%, which is much higher than the highest 74% in the control group. The mechanical strength is also improved by high-energy ball milling and optimized post-treatment process, which is between 81% and 88%, which is higher than the control group. At the same time, phase inversion preparation and strict control of process parameters make the porosity higher, between 39% and 44%, and the pore size distribution better, between 85% and 92%, while the porosity and pore size distribution of the control group are poor.

[0119] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A ceramic membrane anti-fouling membrane layer for sewage treatment, characterized in that: Including the following ingredients: Ceramic powder: 40-60 parts; Nano titanium dioxide: 8-17 parts; Polyethersulfone: 12-20 parts; Surfactant: 1-3 parts; Antibacterial agent: 0.8-2 parts; Organic solvent: 1-3 parts; Tea polyphenols powder: 6-12 parts.

2. The ceramic membrane anti-fouling membrane layer for sewage treatment according to claim 1, characterized in that: The antibacterial agent is a silver ion antibacterial agent; the surfactant is sodium dodecyl sulfate; and the organic solvent is N,N-dimethylformamide.

3. The ceramic membrane anti-fouling membrane layer for sewage treatment according to claim 1, characterized in that: The tea polyphenol powder comprises ingredients of catechins, flavonoids and flavonols, phenolic acids, anthocyanins and citric acid, wherein the amount of citric acid in the tea polyphenol powder is 5%-15%.

4. A process for preparing the anti-fouling membrane layer of the ceramic membrane for sewage treatment according to claim 1, characterized in that: The following steps are involved: S1. Raw material pretreatment: putting ceramic powder and nano titanium dioxide into a high-energy ball mill for grinding, so that the particle size of the ceramic powder and nano titanium dioxide reaches the nanometer level; S2. Mixing and stirring: Add the pretreated ceramic powder and nano titanium dioxide, as well as polyethersulfone, surfactant, antibacterial agent and tea polyphenol powder into a clean stirring container in sequence, then add the organic solvent, stir with a stirrer, and check the uniformity of the mixed material by sampling and testing; S3, preparation of casting solution: transferring the mixed materials to a heating container for heating, stirring the materials continuously during the heating process to fully dissolve the polyethersulfone to form a casting solution, and then transferring the casting solution to a vacuum degassing device for vacuum degassing to remove bubbles in the casting solution, and controlling the vacuum degree and degassing time; S4, membrane preparation: a ceramic membrane anti-fouling membrane layer is prepared by a phase inversion method, the casting liquid is uniformly coated on a support, and then the support coated with the casting liquid is immersed in a coagulation bath, the temperature of the coagulation bath is 10°C-30°C, so that the solvent in the casting liquid is exchanged with the non-solvent in the coagulation bath, thereby forming a membrane layer with a microporous structure; S5, post-treatment: taking the prepared film layer out of the coagulation bath, placing it in a well-ventilated drying oven for drying, controlling the drying temperature and time, removing the residual solvent, and then heat-treating the dried film layer, placing the film layer in a heat treatment device, and controlling the temperature and time, and then using a plasma treatment device to perform surface modification on the heat-treated film layer to introduce hydrophilic groups; S6. Performance testing: Conduct comprehensive performance testing on the prepared ceramic membrane anti-fouling film layer, including porosity, pore size distribution, anti-fouling performance and mechanical strength.

5. The process for preparing the anti-fouling ceramic membrane layer for sewage treatment according to claim 4, characterized in that: In S1, the rotation speed of the high energy ball mill is 300 r / min-400 r / min, and the grinding time is 4 h-6 h.

6. The process for preparing the anti-fouling ceramic membrane layer for sewage treatment according to claim 4, characterized in that: In S2, the stirring time of the stirrer is 2h-4h, the stirring speed of the stirrer is 100r / min-200r / min, and the state of the mixed material is observed every 30min-40min.

7. The process for preparing the anti-fouling ceramic membrane layer for sewage treatment according to claim 4, characterized in that: In S3, the temperature of the heating container is controlled at 60°C-80°C, and the material is continuously stirred for 1h-2h.

8. The process for preparing the anti-fouling ceramic membrane layer for sewage treatment according to claim 4, characterized in that: In S3, the vacuum degree of the vacuum degassing equipment is -0.06MPa--0.1MPa, and the degassing time is 40min-60min.

9. The process for preparing the anti-fouling ceramic membrane layer for sewage treatment according to claim 4, characterized in that: In S5, the drying temperature of the drying oven is 40°C-60°C, and the drying time is 5h-7h.

10. The process for preparing the anti-fouling ceramic membrane layer for sewage treatment according to claim 4, characterized in that: In S5, the temperature of the heat treatment equipment is controlled at 100° C.-150° C., and the heat treatment time is controlled at 1 h-2 h.

Citation Information

Cited By

  • Preparation method of metal-based ceramic composite membrane with ozone catalysis function

    CN121623584A